Piezoelectric photocatalytic composite membrane driven at low flow rate as well as preparation method and application of piezoelectric photocatalytic composite membrane

By introducing g-C3N4 and MoO3 into PVDF-TrFE, a low-flow-rate driven piezoelectric photocatalytic composite film was formed, which solved the problems of complex and high cost in the preparation of high-quality β-phase PVDF-TrFE films, and achieved efficient photocatalytic hydrogen production and improved piezoelectric performance.

CN119303612AActive Publication Date: 2025-01-14KUNMING UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411430214.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

In the existing technology, the methods for preparing high-quality β-phase PVDF-TrFE piezoelectric films are complex and costly, making them difficult to apply to industrial production. Furthermore, graphitized carbonitride (g-C3N4) photocatalysts have limitations in terms of visible light absorption and carrier recombination rate.

Method used

By combining g-C3N4 and MoO3 with PVDF-TrFE, a low-flow-rate driven piezoelectric photocatalytic composite film is formed. The g-C3N4/MoO3 heterojunction guides the self-polarization process in PVDF-TrFE, increasing the β-phase content, simplifying the preparation process, and improving the photocatalytic performance.

Benefits of technology

It achieves a highly efficient photocatalytic hydrogen production reaction, increasing the hydrogen production rate by 1.87 times, significantly enhancing piezoelectric properties, and is low in cost and easy to industrialize.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303612A_ABST
    Figure CN119303612A_ABST
Patent Text Reader

Abstract

The invention provides a piezoelectric electro-catalytic composite membrane driven at a low flow rate as well as a preparation method and application thereof, and belongs to the technical field of dielectric materials. The preparation method provided by the invention comprises the following steps: uniformly mixing g-C3N4 and MoO3 with a solvent to obtain a mixture; sequentially drying, grinding and sintering the mixture to obtain a g-C3N4 / MoO3 composite material; and dispersing the g-C3N4 / MoO3 composite material and PVDF-TrFE in an organic solvent, then coating a matrix material with the obtained dispersion liquid, and then drying the matrix material to obtain the piezoelectric electro-catalytic composite membrane driven at the low flow rate. The preparation method provided by the invention is simple, meanwhile, the formation of high-quality beta-phase PVDF-TrFE can be promoted, and the obtained piezoelectric electro-catalytic composite membrane has high photocatalytic HER efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of dielectric materials, and in particular to a low-flow-rate driven piezoelectric photocatalytic composite membrane and a preparation method and application thereof. Background Art

[0002] The increasing depletion of non-renewable energy resources is exacerbating the global energy crisis. The pioneering work of Fujishima and Honda revealed the potential of TiO2 for photocatalytic hydrogen production, providing a new solution for sustainable energy generation. This discovery reveals the potential of semiconductors in photocatalytic water splitting, providing a promising strategy to alleviate energy shortages. Recently, heterojunctions composed of graphitized carbon nitride (g-C3N4) have been used as efficient photocatalysts for hydrogen production, but their performance is hampered by poor visible light absorption and high carrier recombination rates. Methods to improve the photocatalytic activity of heterojunctions, such as surface morphology regulation and defect engineering, have shown promise but are limited by factors such as the electric field and limited tuning capabilities. In this context, the internal polarization electric field of piezoelectric materials has attracted academic attention in recent years. Many studies have been devoted to elucidating the impact of this built-in field on carrier dynamics and lifetime, as well as its potential to enhance photocatalytic processes.

[0003] PVDF-TrFE is known for its excellent mechanical toughness, chemical stability and significant piezoelectric constant, making it an excellent substrate for photocatalysts. The β phase of PVDF-TrFE is crucial for improving piezoelectric capabilities because of its superior electroactivity over the α phase. Therefore, researchers have proposed a variety of techniques for manufacturing PVDF-TrFE, including electrospinning, mechanical stretching, mechanical pressure, and polarization in a strong electric field to promote the formation of high-quality β-phase PVDF-TrFE. However, these manufacturing processes are very complicated and usually costly, making them difficult to apply to actual industrial production. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a low-flow-rate driven piezoelectric photocatalytic composite membrane and its preparation method and application. The preparation method provided by the present invention is simple and can promote the formation of high-quality β-phase PVDF-TrFE. The obtained piezoelectric photocatalytic composite membrane has high photocatalytic HER efficiency.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is a method for preparing a low-flow-rate driven piezoelectric photocatalytic composite membrane, comprising the following steps:

[0007] Step 1. Evenly mix g-C3N4 and MoO3 with a solvent to obtain a mixture;

[0008] Step 2. drying, grinding and sintering the mixture in sequence to obtain a g-C3N4 / MoO3 composite material;

[0009] Step 3. Disperse the g-C3N4 / MoO3 composite material and PVDF-TrFE in an organic solvent, then apply the resulting dispersion on a substrate material, and then dry it to obtain the low-flow-rate driven piezoelectric photocatalytic composite membrane.

[0010] The second technical solution of the present invention is a low-flow-rate driven piezoelectric photocatalytic composite membrane prepared by the above-mentioned preparation method.

[0011] A third technical solution of the present invention is an application of the above-mentioned low-flow-rate driven piezoelectric photocatalytic composite membrane in photocatalytic hydrogen production.

[0012] The present invention discloses the following technical effects:

[0013] The preparation method provided by the invention is simple, low in cost and easy to realize industrial production.

[0014] The low-flow-rate driven piezoelectric photocatalytic composite membrane provided by the present invention has enhanced piezoelectric properties and can be used for photocatalytic hydrogen production reaction (HER). The present invention can form a PVDF-TrFE composite membrane with more piezoelectric β phase by adding g-C3N4 / MoO3 by inducing the deflection of the CH2 bond. Under low-speed water flow drive, the hydrogen production rate of the piezoelectric photocatalytic composite membrane of the present invention is increased by 1.87 times. The pressure current test also shows that under the same pressure conditions, this piezoelectric photocatalytic composite membrane has a higher current response than PVDF-TrFE. The present invention provides a new solution for preparing high-performance piezoelectric materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 The structures and micromorphologies of MoCNP-50 and PVDF-TrFE in the effect verification example, where (a) is the SEM of PVDF-TrFE, (b) is the SEM of MoCNP-50, (c) is the EDS spectrum of MoCNP-50, (d) is the distribution of C in MoCNP-50, (e) is the distribution of F in MoCNP-50, (f) is the distribution of Mo in MoCNP-50, (g) is the distribution of N in MoCNP-50, and (h) is the distribution of O in MoCNP-50.

[0017] Figure 2 Powder XRD patterns of MoCN-50, PVDF-TrFE and MoCNP-50 in the effect verification example.

[0018] Figure 3 FT-IR graph of MoCNP-50 in the effect verification example, where (a) is the transmission spectrum of MoCNP-50 and PVDF-TrFE, and (b) is the absorption spectrum and β-phase content of MoCNP-50 and PVDF-TrFE.

[0019] Figure 4 The XPS graphs of MoCNP-50 in the effect verification example, where (a) is the C1s spectrum of MoCNP-50, and (b) is the Mo 3d spectrum of MoCNP-50.

[0020] Figure 5 Schematic diagram of the structure of MoCNP-50 and PVDF-TrFE.

[0021] Figure 6 This is a comparison chart of the photocatalytic water decomposition hydrogen production performance test of different materials in the effect verification example, where (a) is the change of photocatalytic hydrogen production of different materials over time, and (b) is the hydrogen production rate of different materials.

[0022] Figure 7 PFM analysis results of MoCNP-50 and PVDF-TrFE in the effect verification example, where (a) is the piezoelectric hysteresis curve of the PVDF-TrFE sample, (b) is the butterfly curve of the PVDF-TrFE sample, (c) is the piezoelectric hysteresis curve of the MoCNP-50 sample, and (d) is the butterfly curve of the MoCNP-50 sample.

[0023] Figure 8 The piezoceramic current of the same MoCNP membrane at different flow rates and different MoCNP membranes at the same flow rate in the effect verification example, where (a) is the piezoceramic current of the same MoCNP membrane under different flow rates, (b) is the piezoceramic current of different MoCNP membranes at the same flow rate, and (c) is the d of PVDF-TrF and MoCNPE 33 value. DETAILED DESCRIPTION

[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0025] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0026] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0027] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0028] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0029] Compared with the existing piezoelectric film preparation methods with complex manufacturing processes and high costs (including electrospinning, mechanical stretching, mechanical pressure and polarization in a strong electric field), the self-polarization of PVDF-TrFE membranes provides a simple and environmentally friendly alternative. By incorporating fillers into PVDF-TrFE, the content of β phase in the membrane is increased by inducing self-polarization.

[0030] Specifically, the present invention provides a method for preparing a low-flow-rate driven piezoelectric photocatalytic composite membrane, comprising the following steps:

[0031] Step 1. Evenly mix g-C3N4 and MoO3 with ethanol to obtain a mixture;

[0032] Step 2. The mixture is dried, ground, and sintered in sequence to obtain a g-C3N4 / MoO3 composite material (denoted as MoCN);

[0033] Step 3. Disperse the g-C3N4 / MoO3 composite material and PVDF-TrFE in an organic solvent, then apply the resulting dispersion on a substrate material, and then dry to obtain the low-flow-rate driven piezoelectric photocatalytic composite membrane (denoted as MoCNP).

[0034] In a preferred embodiment of the present invention, the preparation method of g-C3N4 is: pyrolyze melamine at 620-660°C (further preferably, 650°C) for 2h to obtain the g-C3N4; the heating rate during the pyrolysis is 5-6°C / min (further preferably, 5°C / min).

[0035] In a preferred embodiment of the present invention, the preparation method of MoO3 is: dissolving (NH4)2MoO4 and citric acid in 2-mercaptoethanol (2-ME), then reacting the resulting solution at 480-520°C for 10-12h (further preferably, reacting at 500°C for 12h), naturally cooling to room temperature after the reaction, and collecting the product, which is the MoO3.

[0036] In a preferred embodiment of the present invention, in step 1, the mass volume ratio of the g-C3N4 and MoO3 to the solvent is 0.05-0.50 g: 0.50-0.95 g: 50-70 mL (further preferably, 0.40-0.50 g: 0.50-0.602 g: 50-70 mL); the solvent is ethanol. The present invention has no special requirements for the uniform mixing method, and the commonly used technical means by those skilled in the art can be selected, for example: ultrasonic treatment, the power of the ultrasonic treatment is 35-40 kHZ, and the time is 2.5-3 hours.

[0037] In a preferred embodiment of the present invention, in step 2, the drying temperature is 60-80°C (further preferably, 60°C), and the time is 12-14h (further preferably, 12h); the sintering temperature is 280-300°C (further preferably, 300°C), and the time is 3.5-4h (further preferably, 4h).

[0038] In the present invention, if the sintering temperature is too high, g-C3N4 will decompose, and if the sintering temperature is too low, g-C3N4 will not be well combined with MoO3. Sintering temperature that is too high or too low will evenly affect the performance of the obtained MoCNP.

[0039] In a preferred embodiment of the present invention, in step 3, the organic solvent is dimethyl sulfoxide (DMSO); the mass volume ratio of the g-C3N4 / MoO3 composite material and PVDF-TrFE to the organic solvent is 45-55mg:240-260mg:2mL (further preferably, 50mg:250mg:2mL); the coating method is spin coating, and the rotation speed during spin coating is 500rpm; the drying parameters are set to: drying at 15-25°C for 3-4 hours. The present invention has no special requirements for the way in which the g-C3N4 / MoO3 composite material and PVDF-TrFE are dispersed in the organic solvent. The technical means commonly used by those skilled in the art can be selected, such as stirring, and the stirring time is 12h to ensure uniform dispersion. The present invention does not specifically limit the selection of the base material. The base material commonly used by those skilled in the art can be selected, such as a glass slide.

[0040] The present invention promotes the self-polarization process by drying. If the temperature is higher than the parameter range of the present invention, the self-polarization process will be affected, and the formation ratio of the piezoelectric β phase of the PVDF itself will be reduced.

[0041] The principle of the present invention is as follows: The present invention incorporates the synthesized g-C3N4 / MoO3 heterojunction (MoCN) into PVDF-TrFE, and then dries it to promote the self-polarization process. This self-polarization phenomenon mainly originates from the strong electrostatic interaction between the positively charged -CH2 group on the PVDF-TrFE polymer chain and the negatively charged MoO3. The obtained g-C3N4 / MoO3PVDF-TrFE membrane (i.e., the low flow rate driven piezoelectric photocatalytic composite membrane, MoCNP) exhibits excellent hydrogen production capacity. The present invention clarifies the mechanism of how the addition of fillers increases the β-phase content in PVDF-TrFE, and promotes the development of low-cost, high-performance PVDF-TrFE membrane material manufacturing technology through a simple method.

[0042] The present invention also provides a low-flow-rate driven piezoelectric photocatalytic composite membrane prepared by the preparation method described in the above technical solution.

[0043] The present invention also provides an application of the low-flow-rate driven piezoelectric photocatalytic composite membrane described in the above technical solution in photocatalytic hydrogen production.

[0044] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0045] Unless otherwise specified, the raw materials and reagents used in the examples can be obtained through commercial channels.

[0046] Example 1

[0047] Step 1. Preparation of g-C3N4: Melamine was placed in an alumina crucible and then heated to 650°C in a muffle furnace at a heating rate of 5°C / min and maintained for 2 h.

[0048] Step 2. Preparation of MoO3: First, 1 g (NH4)2MoO4 and 3 g citric acid were added to 10 ml of 2-ME, and the mixture was thoroughly stirred for 4 hours to ensure homogeneity. Subsequently, the solution was allowed to stand for 48 hours to achieve complete dissolution. Then, the solution was placed in a muffle furnace and heated to 500°C at a heating rate of 5°C / min for 12 hours. After the heating process was completed, the sample was naturally cooled to room temperature.

[0049] Step 3. Preparation of MoCN: First, 0.50g of g-C3N4 prepared in step 1 and 0.50g of MoO3 prepared in step 2 were added to 50mL of ethanol and ultrasonically treated for 3 hours. Subsequently, the mixture was dried at 60°C for 12 hours. Finally, the powders were mixed and thoroughly ground for 0.5 hours and then sintered at 300°C for 4 hours. The product was obtained after cooling and named MoCN. According to the synthesis route, g-C3N4 / MoO3 composite materials with different MoO3 weight percentages of 5wt% (prepared from 0.05g g-C3N4 and 0.95g MoO3) and 50wt% (prepared from 0.50g g-C3N4 and 0.50g MoO3) were synthesized respectively. The resulting MoCN composite materials were named MoCN-5 and MoCN-50, respectively.

[0050] Step 4. Preparation of MoCNP: 50 mg of MoCN was added to 2 ml of DMSO and ultrasonicated for 30 minutes, followed by the addition of 250 mg of PVDF-TrFE powder and stirring for 12 hours to ensure dispersion. The mixture was then spin-coated on a 2.5 cm × 2.5 cm glass slide using a spin coater at a speed of 500 rpm. Finally, the coated product was dried at room temperature (within the range of 15 to 25 ° C) for 4 hours to obtain a g-C3N4 / MoO3 / PVDF-TrFE membrane, denoted as MoCNP. Depending on the different types of MoCN used, the resulting membranes were named MoCNP-5 and MoCNP-50, respectively.

[0051] Effect verification example

[0052] The structure and micromorphology of MoCNP-50 and PVDF-TrFE were observed by SEM. Figure 1 As shown. It is observed that the pore distribution within MoCNP-50 is relatively uniform and the pore size is small. Figure 1As shown in (cf), EDS analysis revealed the distribution of various elements of g-C3N4 and MoO3 in MoCNP, confirming the successful synthesis of g-C3N4 / MoO3 / PVDF-TrFE composites by PVDF-TrFE, g-C3N4 and MoO3.

[0053] Powder XRD patterns of MoCN-50, PVDF-TrFE and MoCNP-50 are shown in Figure 2 As shown. The XRD pattern confirmed the formation of the photocatalyst. The XRD peaks of the g-C3N4 sample matched well with those of g-C3N4 (JCPDS 871526), ​​with two well-defined peaks at 27.6° and 13.8°, which were the (002) and (100) diffraction planes. Comparing PVDF-TrFE and MoCNP-50, it can be found that after the introduction of MoCN-50 into PVDF-TrFE, the 20.1° peak corresponding to the β phase of PVDF-TrFE became sharper, while the peak corresponding to the α phase was weaker than that of PVDF-TrFE. This indicates that part of the α phase of PVDF-TrFE is transformed into the β phase.

[0054] In order to clarify the mechanism of β-phase enhancement, FT-IR test was performed on MoCNP-50 (in the figure, MoCNP represents MoCNP-50). Figure 3 (a), 2800-3600cm -1 The absorption band in the region corresponds to the NH group of the unreacted amine, 1240–1650 cm -1 The absorption bands in the region represent CN and C=N bonds, 950cm -1 and 1014cm -1 The peak at belongs to MoO3. All these indicate that MoCN-50 is successfully loaded onto PVDF-TrFE. Figure 3 Figure (b) shows that the α phase is at 760 cm -1 The peak of the α phase disappeared at 810 cm -1 The peak of weakened with the addition of MoCN-50. At the same time, the content of β phase increased from 55.1% to 81.8%, proving the effect of MoCN-50 addition on the phase composition of PVDF-TrFE.

[0055] The composition of MoCNP-50 composites was further characterized using XPS. Figure 4As shown in (a) (in the figure, MOCNP represents MoCNP-50), the C1s spectrum of MoCNP-50 can be decomposed into four peaks at 284.8eV (CC bond), 286.3eV (CH2 bond), 288.7eV (CF bond) and 290.9eV (CF2 bond). At the same time, the Mo 3d spectrum (Figure (b)) clearly shows peaks at 231.4eV and 234.5eV, which are attributed to Mo 5+ , and peaks at 232.8 eV and 235.8 eV, corresponding to Mo 6+ At the same time, the spectral examination revealed the shift of CH2 bonds to lower binding energy, while CF and CF2 bonds and Mo shifted to higher binding energy. This phenomenon indicates that there is a directional charge transfer between MoO3 and CH2 bonds, which indicates a strong electrostatic interaction. Due to this electrostatic interaction, the CH2 bond rotates, such as Figure 5 As shown, this leads to an increase in the β-phase content in PVDF-TrFE.

[0056] like Figure 6 As shown in (a) and (b), under the same conditions, the MoCNP-50 piezoelectric film exhibits a conductivity of 552.4 μmol h -1 This rate is significantly higher than that of the powder catalyst MoCN-50 (302.16 μmol h -1 The performance of the MoCNP-50 membrane under stationary conditions without stirring was further examined. With all other parameters kept constant, the HER rate dropped significantly to 231.63 μmol h -1 The significant reduction in the HER rate provides strong evidence for the generation of a piezoelectric field in MoCNPs due to water flow. The mechanical stress of the water flow is converted into electrical energy through the piezoelectric effect, generating a potential difference that promotes the effective separation of photogenerated electron-hole pairs, thereby improving the efficiency of photocatalytic HER.

[0057] In addition, we tested the hydrogen production capacity of the MoCNP-5 piezoelectric film and its corresponding powder catalyst (MoCN-5). The study found that although the MoCNP-5 piezoelectric film and powder catalyst have relatively high hydrogen production capacity under static conditions, their hydrogen production rate and enhancement ratio are significantly lower than those of the MoCNP-50 piezoelectric film under the same water flow drive. This shows that a higher MoO3 concentration is conducive to the piezoelectric film to achieve a higher hydrogen production rate under water flow drive. That is, MoO3 can enhance the β-phase content of PVDF-TrFE.

[0058] PFM was used to characterize the piezoelectric properties of MoCNP-50 and PVDF-TrFE samples. Figure 7PFM analysis produces a characteristic butterfly curve, which indicates the piezoelectric response of the material. These features are consistent with the phenomenon of charge generation when mechanical stress is applied, which is a hallmark of piezoelectric materials. Comparative analysis of the PFM data shows that MoCNP-50( Figure 7 (c) and (d)) and PVDF-TrFE ( Figure 7 Compared with (a) and (b), MoCNP-50 exhibits a more pronounced piezoelectric response. The piezoelectric response amplitude of MoCNP-50 is significantly higher, as can be seen from the larger butterfly curve. This enhancement of the piezoelectric signal clearly indicates the enhanced ability of MoCNP to convert mechanical stimulation into electrical energy, indicating its superior piezoelectric performance relative to PVDF-TrFE. This enhanced piezoelectric response is due to its higher β-phase content.

[0059] In addition, we measured the piezoresistance on the same photocatalytic film at different flow rates, and measured the piezoresistance on different photocatalytic films at the same flow rate ( Figure 8 ). Our findings reveal that the prepared MoCNP photocatalytic membrane is highly sensitive to flow rate, and the piezoceramic current increases positively with the increase in flow rate. In addition, the comparison of the piezoceramic currents of MoCNP and PVDF-TrFE membranes at the same flow rate shows that the reaction of the PVDF-TrFE photocatalytic membrane is not as obvious. At the same time, we tested the D 33 The coefficient of MoCNP is directly proved to have better piezoelectric response than PVDF-TrFE. The piezoelectric stress test results confirmed that the piezoelectric sensitive β phase in PVDF-TrFE is the key factor affecting the piezoelectric performance, which determines that the PVDF-TrFE film enhanced with MoCN has higher HER activity.

[0060] The above results show that high photocatalytic HER efficiency is achieved by introducing MoCN into PVDF-TrFE. The study found that the strongly electronegative MoO3 has a profound effect on the structure of the PVDF-TrFE chain. Through electrostatic interactions, the CH2 bond rotation is induced, thereby increasing the proportion of β phase in the PVDF-TrFE chain. Therefore, MoCNPs exhibit significantly better photocatalytic HER efficiency under pressure than unstressed MoCNPs. Subsequent studies using PFM and pressure current measurements revealed that under the influence of low-speed water flow, MoCNPs produce a stronger built-in electric field and more effectively promote the separation of charge carriers. The present invention provides a new route for the simple manufacture of materials with excellent piezoelectric properties, which is of great significance for the development of advanced energy conversion technologies.

[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a low-flow-rate driven piezoelectric photocatalytic composite membrane, characterized in that: The following steps are involved: Step 1. Evenly mix g-C3N4 and MoO3 with a solvent to obtain a mixture; Step 2. The mixture is dried, ground and sintered in sequence to obtain a g-C3N4 / MoO3 composite material; Step 3. Disperse the g-C3N4 / MoO3 composite material and PVDF-TrFE in an organic solvent, then apply the resulting dispersion on a substrate material, and then dry it to obtain the low-flow-rate driven piezoelectric photocatalytic composite membrane.

2. The method for preparing a low-flow-rate driven piezoelectric photocatalytic composite membrane according to claim 1, characterized in that: The preparation method of g-C3N4 is as follows: melamine is pyrolyzed at 620-660°C for 2h to obtain the g-C3N4; the heating rate during the pyrolysis is 5-6°C / min.

3. The method for preparing a low-flow-rate driven piezoelectric photocatalytic composite membrane according to claim 1, characterized in that: The preparation method of the MoO3 is: dissolving (NH4)2MoO4 and citric acid in 2-ME, then reacting the resulting solution at 480-520°C for 10-12h, naturally cooling to room temperature after the reaction, and collecting the product, which is the MoO3.

4. The method for preparing a low-flow-rate driven piezoelectric photocatalytic composite membrane according to claim 1, characterized in that: In step 1, the mass volume ratio of the g-C3N4 and MoO3 to the solvent is 0.05-0.50 g: 0.50-0.95 g: 50-70 mL; and the solvent is ethanol.

5. The method for preparing a low-flow-rate driven piezoelectric photocatalytic composite membrane according to claim 1, characterized in that: In step 2, the drying temperature is 60-80° C. and the time is 12-14 hours; the sintering temperature is 280-300° C. and the time is 3.5-4 hours.

6. The method for preparing a low-flow-rate driven piezoelectric photocatalytic composite membrane according to claim 1, characterized in that: In step 3, the organic solvent is dimethyl sulfoxide; the mass volume ratio of the g-C3N4 / MoO3 composite material and PVDF-TrFE to the organic solvent is 45-55 mg:240-260 mg:2 mL; the drying parameters are set as: drying at 15-25°C for 3-4 hours.

7. A low-flow-rate driven piezoelectric photocatalytic composite membrane prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the low-flow-rate driven piezoelectric photocatalytic composite membrane according to claim 7 in photocatalytic hydrogen production.

Citation Information

Patent Citations

  • Carbon dot-molybdenum trioxide and carbon nitride composite catalyst, preparation method and applications thereof

    CN107803215A

  • CN / LiNbO3 / PVDF piezoelectric photocatalysis composite membrane as well as preparation method and application thereof

    CN112371175A

  • Method for preparing orthorhombic-phase molybdenum trioxide through one-step sintering method

    CN115196680A

  • Composite photocatalyst C-MoO2 / C3N4 as well as preparation method and application thereof

    CN115779951A

  • Piezoelectric electro-catalysis MoO3 / P (VDF-TrFE) nano composite membrane as well as preparation method and application thereof

    CN116747902A